The effect of limited access to antenatal care on pregnancy experiences and outcomes among undocumented migrant women in Europe: a systematic review - Osuide, Jennifer Okhianosen; Parsa, Ali Davod; Mahmud, Ilias; Kabir, Russell (Frontiers in Global Women's Health, 2024)
Women who are undocumented migrants in Europe encounter a variety of challenges while trying to access health services, including restricted access to antenatal care (ANC) despite the importance of ANC to the well-being of mothers and their infants. This study's aim was to examine the effect that limited access to antenatal care has on the pregnancy experiences and outcomes of undocumented migrant(UM) women in Europe. Systematic searches were done on PubMed, Ovid MEDLINE, Ovid EMBASE, EBSCO CINAHL Plus, and BioMed Central. From the search results, only primary research articles that reported on the pregnancy outcomes and experiences of undocumented migrants were selected. A meta-analysis was not possible because this review included information from both qualitative and quantitative studies. The data that was taken from the included publications was organised, analysed, using the Microsoft Excel programme, and then meta-synthesised. Twelve papers from seven different European nations-Belgium, France, Sweden, Denmark, Norway, Finland, and England-were included in this systematic review. Eight of the studies aimed to explore the access to and utilization of ANC by undocumented migrant women and the related pregnancy outcomes. Two of the included studies examined the pregnancy experiences of UMs and two examined the perinatal risks associated with living as a migrant with no legal status. Although heterogeneous in their specific findings most of the studies showed Undocumented immigrants are more likely to experience unfavourable pregnancy outcomes and experience greater anxiety and worries due to a variety of factors than documented migrants and registered citizens. This review's conclusions demonstrate the pressing need for policy. modifications and healthcare reforms in Europe to address the problems associated with undocumented migrants' restricted access to antenatal care. They also highlight the urgent need for structural changes that will give this vulnerable population's health and well-being a higher priority. It is not just an issue of health equality but also a humanitarian obligation to address the many obstacles and difficulties undocumented migrant women endure during pregnancy.